2014
DOI: 10.1371/journal.pone.0093100
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Mutational Analysis of Omega-Class GST (GSTO1) from Apis cerana cerana, a Gene Involved in Response to Oxidative Stress

Abstract: The Omega-class of GSTs (GSTOs) is a class of cytosolic GSTs that have specific structural and functional characteristics that differ from those of other GST groups. In this study, we demonstrated the involvement of the GSTO1 gene from A. cerana cerana in the oxidative stress response and further investigated the effects of three cysteine residues of GSTO1 protein on this response. Real-time quantitative PCR (qPCR) showed that AccGSTO1 was highly expressed in larvae and foragers, primarily in the midgut, epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…In cancer tissue, inflammation has been triggered and angiogenesis is extensive, therefore further reactive oxygen species are produced. A recent study identified that GSTO1 provides protection from oxidative stress (20). This result is consistent with the results of the present study that DISS cells that expressed increased levels of GSTO1 responded well to PDT.…”
Section: Signal -------------------------------------------------------supporting
confidence: 94%
“…In cancer tissue, inflammation has been triggered and angiogenesis is extensive, therefore further reactive oxygen species are produced. A recent study identified that GSTO1 provides protection from oxidative stress (20). This result is consistent with the results of the present study that DISS cells that expressed increased levels of GSTO1 responded well to PDT.…”
Section: Signal -------------------------------------------------------supporting
confidence: 94%
“…Recently, a role for insect GSTs in mediating the oxidative stress response has been suggested by a number of studies (eg Yan et al ., ; Meng et al ., ). For example, in venom glands of Apis mellifera , proteomic analysis indicated that the presence of GSTs seems to defend against oxidative stress (Peiren et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The number of Cys residues that each GSTO protein contains varies within species. For instance, human GSTO2 has 11 Cys residues compared with five in GSTO1 (Zhou et al ., ), whereas Apis cerana cerana GSTO1 and GSTO2 both have three Cys residues (Meng et al ., ). Several studies have demonstrated that the site‐directed mutagenesis of active site Cys residues can result in undetected or decreased enzymatic activity toward GSTOs (Burmeister et al ., ; Yamamoto et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…5A-D). Some of those genes belong to the thioredoxin family, such as Trx-1, Trx1-like2 and Trxr-1, as well as the glutaredoxin and glutathione families, all known to be involved with Apis cerana's response to oxidative stress (Meng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%